A novel hydrophobic ZrO2-SiO2 based heterogeneous acid catalyst for the esterification of glycerol with oleic acid / Kong Pei San - Kong , Pei San (2018)
The inevitably low value of glycerol has led to extensive investigations on glycerol conversion to value-added derivatives. This work focuses on industrially important catalytic esterification of glycerol with oleic acid due to its high commercial value. In this work, a novel heterogeneous acid catalyst featuring hydrophobic surface was developed on ZrO2-SiO2 support as water tolerant solid acid catalyst is vital for two phase esterification reactions producing water. The synthesized catalyst (ZrO2-SiO2-Me&Et-PhSO3H) was prepared through silication and surface modification using trimethoxymethylsilane (TMMS) and 2-(4-chlorosulfonylphenyl)ethyltrimethoxysilane. The surface morphology, physiochemical and textural properties, acidity and hydrophobicity were characterized. The mechanism of the catalyst surface modification is thereof proposed according to comprehensive characterization results. A novel technique to control acidity and hydrophobicity level of the designed catalyst is disclosed in this work. The acidity and hydrophobicity of the catalyst were tuned by controlling the amount of surface modification agents. It was found that the hydrophobicity of the catalyst is decreased as its acidity increased. ZrO2-SiO2-Me&Et-PhSO3H_70 catalyst with 70 mol% of TMMS and 0.62 mmol/g acidity is the optimal catalyst for glycerol esterification with oleic acid. Furthermore, the role of hydrophobicity in catalytic reaction was investigated herein. It was found that at constant catalyst acidity, the more hydrophobic catalyst showed better yield. The conversion obtained with the designed catalyst (ZrO2-SiO2-Me&EtPhSO3H_70) is 88.2% with 53.5% glycerol monooleate selectivity and 40.0% glycerol dioleate selectivity (combined 94% selectivity of glycerol monooleate and dioleate) at equimolar oleic acid-to-glycerol ratio, 160 oC, reaction temperature, 5 wt% catalyst concentration with respect to weight of oleic acid, solvent-less reaction conditions and 8 h reaction time. This work reveals hydrophobicity and pore volume of the designed catalyst affect the selectivity of product significantly. In addition, the performance of the hydrophobic designed ZrO2-SiO2-Me&Et-PhSO3H_70 catalyst was used to benchmark with catalytic activity of sulfated zirconia (SO42-/ZrO2) and commercial catalysts (Amberlyst 15 and Aquivion). The correlation results showed that pore volume (pore size) influenced the product selectivity when ZrO2-SiO2-Me&Et-PhSO3H_70 catalyst was compared to three SO42-/ZrO2 catalysts that were developed from different zirconium precursors. Whereby, the higher pore volume catalyst is favourable to glycerol dioleate production at identical reaction conditions. It can be concluded pore volume and size can be used to control the selectivity of the products. In addition, this study also revealed hydrophobicity characteristic facilitated initial reaction rate effectively.